THE EFFECT OF STAD METHOD IN WRITING DISCUSSION TEXT ABILITY AT THE XII GRADE STUDENTS OF SMA NEGERI 1 SIPIROK - Ester Hutabarat (JURNAL LINER (Language Intelligence and Educational Research), 2018)
Abstract The aim of this research is to find out whether there is any significant effect of STAD method in writing discussion text ability to the twelfth grade students of SMA Negeri 1 Sipirok. In order to achieve the aim of this research, the writer carried the quantitative approach by applying experimental method. The population was the twelfth Grade Students of SMA Negeri 1 Sipirok, which consists of 150 students. The writer used cluster sampling technique to get the sample. The whole amount samples were 60 students. The data was collected by using composition test as an instrument. The writer used statistic processes in analyzing data. They were descriptive and inferential analysis by using the formula of “t-test”. After calculating the data, it was found thatthe mean score of students’ writing discussion text before using STAD methodis69.84, it is categorized “enough”. While the mean score of students’ writing discussion text after using STADis 75.93, it is categorized “good”. The result of the analyzed data shows that to is greater than ttor (3.15> 2.00). So, the hypothesis is accepted. It means there is a significant effect of STAD method to students’ writing discussion text ability (a study to the twelfth grade students of SMA Negeri 1 Sipirok). Keywords: STAD Method, Writing Ability, Discussion Text